Eksplorasi Kendala Guru dalam Pengajaran Bahasa Inggris di SD 101774 Medan Estate Deli Serdang - Raiga Yesica Br Manalu; Ancya Insari Sidabutar; Fransiskus Temaziduhu Gulo; Nazra Haura Nadzifa; Yoslin Wijaya (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to identify the challenges faced by teachers in teaching English at SDN 101774 Medan Estate, Deli Serdang, especially related to low student interest in learning and difficulties in understanding Question Words (5W + 1H) material. This study uses a survey method with data collection techniques through direct observation and in-depth interviews with class teachers and students. The results of the study indicate that limited understanding, low student memory, and lack of active involvement in the learning process are the main obstacles in learning English. To overcome these difficulties, teachers apply various strategies such as peer dialogue, the use of picture dictionaries, gradual vocabulary memorization methods, and fun learning approaches through educational games. These strategies have been proven to help increase students' interest in learning and understanding of the material. The implications of this study emphasize the importance of innovation in learning methods and the active role of teachers in creating an interesting, interactive, and appropriate learning atmosphere for elementary school students.